Establishing Population Pharmacokinetic Model for Pyrazinamide in Pulmonary Tuberculosis Patients - Phan Tuan Duc; Bui Son Nhat; Le Thi Luyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
In this study, a reasonable population pharmacokinetic model with influencing covariates for pyrazinamide was established based on the data of 129 pulmonary tuberculosis patients in 3 hospitals: Hanoi Lung Hospital, K74 Hospital, and Central Lung Hospital. Blood samples were obtained on the 10-14th day after initiation of treatment. Time-concentration data were incorporated into the software MONOLIX 2019R2 for model building by non-linear mixed effect modeling method. The final population pharmacokinetic model is a one-compartment model, first-order absorption with lag time (Ka = 3.99 h-1, Tlag = 0.445 h), linear elimination, volume of distribution V = 27.5 L, and clearance rate Cl = 2.65 L/h. Janmahasatian’s Fat-free mass was found to be influential to the inter-individual variability of volume of distribution and rate of clearance. Keywords Population pharmacokinetic, pyrazinamide, pulmonary tuberculosis, fat-free mass. References [1] World Health Organization, Global Tuberculosis Report 2020, https://www.who.int/publications-detail-redirect/9789240013131 (accessed on: May 7th, 2021).[2] C. Lienhardt, P. Nahid, M. L. Rich et al., Target Regimen Profiles for Treatment of Tuberculosis: A WHO Document. European Respiratory Journal, Vol. 49, No. 1, 2017, https://doi.org/10.1128/AAC.00490-17.[3] E. F. Egelund, A. Alsultan, C. A. Peloquin, Optimizing the Clinical Pharmacology of Tuberculosis Medications, Clin Pharmacol Ther, Vol. 98, No. 4, 2015 pp. 387-393, https://doi.org/10.1128/AAC.03931-1-4.[4] M. A. Steele, R. M. D. Prez, The Role of Pyrazinamide in Tuberculosis Chemotherapy. Chest, Vol. 94, No. 4, pp. 845-850, 1988, https://doi.org/10.1378/chest.94.4.845.[5] L. T. Luyen, T. M. Hung, L. T. Huyen et al., Simultaneous Determination of Pyrazinamide, Rifampicin, Ethambutol, Isoniazid and Acetyl Isoniazid in Human Plasma by LC-MS/MS Method. Journal of Applied Pharceutical Science, Vol. 8, No. 9, 2018 pp. 061-073, https://doi.org/10.7324/JAPS.2018.8910.[6] R. M. Savic, D. M. Jonker, T. Kerbusch et al., Implementation of A Transit Compartment Model for Describing Drug Absorption in Pharmacokinetic Studies, J Pharmacokinet Pharmacodyn, Vol. 34, No. 5, 2007, pp. 711-726, https://doi.org/ 10.1038/psp.2012.4.[7] S, Janmahasatian, S. B. Duffull, S. Ash et al., Quantification of Lean Bodyweight, Clin Pharmacokinet, Vol. 44, No. 10, 2005, pp. 1051-1065, https://doi.org/10.1016/S0099-5428(08)60173-2.[8] M. T. Chirehwa, H. McIlleron, R. Rustomjee et al., Pharmacokinetics of Pyrazinamide and Optimal Dosing Regimens for Drug-Sensitive and -Resistant Tuberculosis, Antimicrobial Agents and Chemotherapy, Vol. 61, No. 8, 2017, https://doi.org/10.1128/AAC.00490-17.[9] M. T. Abdelwahab, R. Leisegang, K. E. Dooley et al., Population Pharmacokinetics of Isoniazid, Pyrazinamide, and Ethambutol in Pregnant South African Women with Tuberculosis and HIV. Antimicrob Agents Chemother, Vol. 64, No. 3, 2020, https://doi.org/10.1128/AAC.01978-19.[10] P. Denti, K. Jeremiah, E. Chigutsa et al., Pharmacokinetics of Isoniazid, Pyrazinamide, and Ethambutol in Newly Diagnosed Pulmonary TB Patients in Tanzania. PLoS One, Vol. 10, No. 10, 2015, https://doi.org/10.1371/journal.pone.0141002.[11] P. Mugabo, M. Mulubwa, Population Pharmacokinetic Modelling of Pyrazinamide and Pyrazinoic Acid in Patients with Multi-Drug Resistant Tuberculosis. Eur J Drug Metab Pharmacokinet, Vol. 44, No. 4, 2019, pp. 519-530, https://doi.org/ 10.1007/s13318-018-00540-w.[12] A. Alsultan, R. Savic, K.E. Dooley et al., Population Pharmacokinetics of Pyrazinamide in Patients with Tuberculosis. Antimicrobial Agents and Chemotherapy, Vol. 61, No. 6, 2017, https://doi.org/10.1128/AAC.02625-16.[13] H. McIlleron, M. Willemse, H. S. Schaaf et al., Pyrazinamide Plasma Concentrations in Young Children with Tuberculosis, Pediatr Infect Dis J, Vol. 30, No. 3, 2011, pp. 262-265, https://doi.org/10.1097/inf.0b013e3181fbefe1.[14] B. J. Anderson, N. H. G. Holford, Mechanism-Based Concepts of Size and Maturity in Pharmacokinetics, Annu Rev Pharmacol Toxicol, Vol. 48, 2008, pp. 303-332, https://doi.org/10.1146/annurev.pharmtox.48.113006.094708.[15] Ministry of Health, Guideline of Diagnosis, Treatment and of Tuberculosis, 2018 (in Vietnamese).